FAKTOR - FAKTOR RISIKO USIA, ASUPAN TABLET FE DAN STATUS GIZI YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL - Waode Sitti Asfiah Udu; Andi Yulia; Sitti Wahidatun Asryani (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2014)
Gravidarum  anemia  can  increase  the  risk  of  mortality  in  pregnancy .  The  prevalence  of  gravidarum anemia  in  world  is  high  especially  in  developing  country  according  to  data  of  WHO.  This  study  aimed  to identify  the gravidarum anemia risk factors such age, Fe tablet consumption and nutritional status in  pregnant woman at  Poasia’s society health center  region  of Kendari City. This  study used an analytical study with case control design. The case groups in this study are 40 pregnant woman with gravidarum anemia who have Hb<11 gr/dL while pregnant woman with Hb ≥  11 gr/dL are  used as control. Risk factor is assessing by Odds ratio. This study founded that  age have OR = 7.21 (1.48-35.06;  95%), Fe tablet consumption have OR = 27.0 (7.68-94.87;  95%)  and  nutritional  status  have  OR  =  1.92  (0.69-5.33;  95%).  As  conclusions,  age  and  Fe  tablet consumption are risk factors  for  gravidarum anemia while nutritional status is not a risk factor for  gravidarum anemia. Key words: Gravidarum anemia, age, Fe tablet consumption, nutritional status.